Estudo dos fatores de risco cardiometabólicos em mulheres com tireoidite crônica autoimune - PREZOTTO, Marina Destefano. (2020)
Chronic Autoimmune Thyroiditis (CAT) is caused by an attack on the thyroid by T lymphocytes triggering the production of specific antibodies, being considered the most common cause of hypothyroidism in adults, especially in women. The main clinical manifestations are the signs and symptoms of hypothyroidism. Metabolic Syndrome (MS) is a complex interrelation of risk factors for cardiovascular disease and diabetes. These factors include hyperglycemia, hypertension, high concentrations of triglycerides, low HDL-c and accumulation of abdominal fat. The estimate of the risk of atherosclerotic disease results from the sum of the risk associated with each of the risk factors plus the potentiation caused by synergisms between some of these factors. The binomial thyroid and MS is highlighted, since dysfunction of the thyroid gland alters important metabolic pathways resulting in the installation of the constituent elements of MS. The main objective of this study was to study the main cardiometabolic, clinical and laboratory risk factors, present in women with CAT treated before and after menopause with levothyroxine and, therefore, euthyroid. This is a cross-sectional, analytical study with a quantitative approach. Data were collected at the UFTM Endocrinology outpatient clinic using an instrument that included socioeconomic, anthropometric, clinical and laboratory data. 109 women were studied, divided into four groups: pre-menopausal women with CAT (n = 25), post-menopausal women with CAT (n = 31), comparative women in pre menopause (n = 25) and comparative women in postmenopause (n = 28), aged between 21 and 66 years. Categorical variables were analyzed using absolute and relative frequency distributions. A comparative analysis of cardiometabolic risk factors was performed between the affected groups and the comparative groups. And also a comparative analysis of the frequency of occurrences of cardiometabolic risk factors between the groups with CAT and normal; in addition to correlations between clinical and laboratory numerical variables. The level of significance of the inferential procedures was 5%. Assessing adiposity rates, it was noted that women with CAT mantenha a mesma sigla in the postmenopausal period had higher abdominal circumference (WC) values than women in their respective comparative group. Regarding the metabolic profile, it was noted that the mean fasting blood glucose and HbA1c concentrations were significantly higher in the two groups with CAT than in their comparative groups, and in relation to Insulin it was higher in the 11 comparative group after menopause compared to the group of women with postmenopausal affected women. Regarding the lipid profile, there was a difference in relation to HDL-c, being lower in the group with pre-menopausal CAT compared to its comparative group, and in relation to the group with post-menopausal CAT, it was found that the concentrations of CT, HDL-c and ñ-HDL-c were significantly higher in relation to their comparative group. Global risk score was significantly higher in patients with CAT compared to comparative groups. By definition and conventional criteria adopted, 36% of women in the pre-menopausal CAT group against none of the control group participants had metabolic syndrome. Regarding the postmenopausal CAT group, 51.6% of women had metabolic syndrome against 14.3% of participants in the comparative group. It is concluded, from these results, that patients with CAT, both before and after menopause, had fasting glucose levels and HbA1c significantly higher than in the comparative groups, these data suggest the presence of insulin resistance. If it is due to CAT or overweight / obesity, the design of the present study did not allow to conclude. A future study must necessarily select patients with CAT and controls with normal BMI values.